Application of Polymerase Chain Reaction Restriction Fragment Length Polymorphism Technique in Determining the Identity of Several Marine Species in Seafood Products - Lim, Sor Sing (2005)
This study describes an investigation on the application of Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) nucleic acid based technique, as a routine analytical technique to generate DNA fingerprints for 24 fresh marine samples. Data obtained from the DNA fingerprints were used to identify 12 processed marine samples. Samples representative of various species and marine products submitted to different processing conditions were selected to verify the applicability of the techniques. A specific part of mitochondrion (mt) genome, cytochrome b (cytb) gene with 359 base pair (bp) fragment was successfully amplified from all the investigated samples by using ‘universal’ primer pairs. The obtained fragment of cytb gene (359 bp) was digested with different Restriction Endonuclease (RE) resulting in sample specific Restriction Fragment Length Polymorphism (RFLP). A total of 14 fishes, 7 prawns and 3 crabs with the exception of Doublelined tonguesole (Paraplagusia bilineata), Rainbow sardine (Dussumieria acuta), Western king prawn (Metapenaeus latisulcatus), Sharp-rostrum prawn (Parapenaeopsis hardwickii), Giant freshwater prawn (Macrobrachium rosenbergii), Affluent prawn (Thenus orientalis), Giant tiger prawn (Penaeus semisulcatus), Indo-pacific swamp crab (Scylla serrata), Red and Blue swimming crab (Solenocera subnuda) could be differentiated using RE HaeIII, MboII, FokI, and MspI followed by agarose gel electrophoresis. For processed marine samples, only four out of twelve were successfully identified. The DNA of unidentifiable samples may have been degraded during the steps of processing. The RFLP patterns obtained are conclusive even in the mixture of Western king prawn (Metapenaeus latisulcatus) and African threadfin (Alexis alexandrinus) at a ratio of 1:100. Results of this study suggest that the PCR-RFLP based on cytb gene shows a reproducible, rapid and simple method for simultaneous identification of marine samples.